Monocytes and Macrophages in COVID-19 - Knoll, Rainer; Schultze, Joachim L.; Schulte-Schrepping, Jonas (Frontiers in Immunology, 2021)
COVID-19 is a contagious viral disease caused by SARS-CoV-2 that led to an ongoing pandemic with massive global health and socioeconomic consequences. The disease is characterized primarily, but not exclusively, by respiratory clinical manifestations ranging from mild common cold symptoms, including cough and fever, to severe respiratory distress and multi-organ failure. Macrophages, a heterogeneous group of yolk-sac derived, tissue-resident mononuclear phagocytes of complex ontogeny present in all mammalian organs, play critical roles in developmental, homeostatic and host defense processes with tissue-dependent plasticity. In case of infection, they are responsible for early pathogen recognition, initiation and resolution of inflammation, as well as repair of tissue damage. Monocytes, bone-marrow derived blood-resident phagocytes, are recruited under pathological conditions such as viral infections to the affected tissue to defend the organism against invading pathogens and to aid in efficient resolution of inflammation. Given their pivotal function in host defense and the potential danger posed by their dysregulated hyperinflammation, understanding monocyte and macrophage phenotypes in COVID-19 is key for tackling the disease’s pathological mechanisms. Here, we outline current knowledge on monocytes and macrophages in homeostasis and viral infections and summarize concepts and key findings on their role in COVID-19. While monocytes in the blood of patients with moderate COVID-19 present with an inflammatory, interferon-stimulated gene (ISG)-driven phenotype, cellular dysfunction epitomized by loss of HLA-DR expression and induction of S100 alarmin expression is their dominant feature in severe disease. Pulmonary macrophages in COVID-19 derived from infiltrating inflammatory monocytes are in a hyperactivated state resulting in a detrimental loop of pro-inflammatory cytokine release and recruitment of cytotoxic effector cells thereby exacerbating tissue damage at the site of infection.